Acute interstitial pneumonia (Hamman-Rich syndrome) in idiopathic pulmonary fibrosis and bronchoalveolar carcinoma: a case report - Plasek, Jiri; Dvorackova, Jana; Jahoda, Jan; Trulikova, Kristina; Mokosova, Radka; Danek, Tomas; Hrabovsky, Vladimir; Martinek, Arnost (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2011)
AIM: Acute interstitial pneumonia is characterized by rapid progressive dyspnoea degenerating into respiratory failure requiring mechanical ventilation. Acute interstitial pneumonia (AIP) and idiopathic pulmonary fibrosis (IPF) are separate clinic/pathological entities although overlap may be present. It is well-known that patients with IPF have increased risk of lung carcinoma; Adenocarcinoma in connection with IPF is less common. Moreover the subtype of adenocarcinoma, diffuse bronchoalveolar carcinoma has not yet been described. CASE REPORT: We report the case of 45 yr old former hockey player with increased bilateral reticular shadowing on chest radiograph, dyspnoea, velcro-like crackles, restrictive respiratory disease and mixed high-resolution computed tomography finding. During brief in-patient treatment the patient developed acute respiratory failure accompanied by multiorgan failure and disseminated coagulopathy. Deterioration of the microcirculation was followed by loss of peripheral vascular resistance, which was irreversible even with normalization of the blood gases achieved by extracorporeal membrane oxygenation. At autopsy, bronchoalveolar carcinoma in usual interstitial pneumonia (UIP) combined with areas of alveolar damage with hyaline membranes was found. CONCLUSION: This case alerts clinicians to unusual idiopathic pulmonary fibrosis manifestations and its complications. Close collaboration between clinicians, pathologists and laboratory physicians is highly recommended for early diagnosis and appropriate treatment.
Keywords: nádory plic; Pulmonary Fibrosis; Lung Diseases, Interstitial; Lung Neoplasms; intersticiální plicní nemoci; Adenocarcinoma, Bronchiolo-Alveolar; Humans; karcinom bronchiolární; mužské pohlaví; plicní fibróza; lidé; Acute Disease; lidé středního věku; Male; Middle Aged; akutní nemoc